Pengaruh Kinerja Keuangan, Kebijakan Dividen, Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan - Tutik Alawiyah; Kartika Hendra Titisari; Yuli Chomsatu (Politeknik Ganesha Medan, 2022)
This study aims to examine and analyze the effect of financial performance (profitability, liquidity, leverage), dividend policy and managerial ownership on firm value. Manufacturing companies in the consumer goods sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period are the samples in this study. Samples were obtained as many as 9 companies using purposive sampling technique. Multiple linear regression analysis tool. Financial performance is measured using profitability, liquidity, and leverage. The results of the study found that profitability and managerial ownership have an effect on firm value, while liquidity, leverage and dividend policy have no effect on firm value.